Quantitative Assessment of the Intracranial Vasculature of Infants and Adults Using iCafe (Intracranial Artery Feature Extraction) - Chen, Li; Shaw, Dennis W. W.; Dager, Stephen R.; Corrigan, Neva M.; Chu, Baocheng; Kleinhans, Natalia M.; Kuhl, Patricia K.; Hwang, Jenq-Neng; Yuan, Chun (Frontiers in Neurology, 2021)
Comprehensive quantification of intracranial artery features may help to assess and understand regional variations of blood supply during early brain development and aging. We analyzed vasculature features of 27 infants, 13 infants at 7-months (7.3±1.0 month) and 14 infants at 12-months (11.7±0.4 month), and 13 older adults (62.8±8.7 years) to investigate age-related vascular differences as a preliminary study of vascular changes associated with brain development. 3D time-of-flight (TOF) magnetic resonance angiography (MRA) acquisitions were processed in iCafe (a technique to obtain quantitative features of arteries) to characterize intracranial vasculature. Overall, adult subjects were found to have increased ACA length, tortuosity and vasculature density compared to both 7-month-old and 12-month-old infants, as well as MCA length compared to 7-month-old infants. No brain laterality differences were observed for any vascular measures in either infant or adult age groups. Reduced skull and brain sharpness, indicative of increased head motion and brain/vascular pulsation, respectively, were observed in infants but not correlated with length, tortuosity or vasculature density measures. Quantitative analysis of TOF MRA using iCafe may provide an objective approach for systematic study of infant brain vascular development and for clinical assessment of adult and pediatric brain vascular diseases.